The status of research on the biomechanics of swimming - Hay, J. G. (Swimming Science V, 1988)
The purposes of this chapter are (a) to evaluate the present status of research on the biomechanics of swimming and (b) to identify important questions for which answers are still needed. Also considerd is the time that a swimmer takes to complete an event-the ultimate measure of the swimmer's performance. This event time equals the sum of the times taken starting, stroking, and turning. Each of these times is discussed here in turn.